النحت المعاصرة والاستفادة منه في تعليم المفردات اللغة العربية لغير الناطقين بها - Hamim, Hamim; Ma’arif, A. Samsul Ma’arif; Mishbahuddin, Mohamad (UIN Maulana Malik Ibrahim Malang, 2024)
This research aims to have three parts: knowledge of sculpture in general, knowledge of contemporary sculpture in Arabic language vocabulary used in several modern scientific terms, and knowledge of the benefits of sculpture in teaching Arabic language vocabulary to non-native speakers. Research Methodology What researchers use is the qualitative approach, which is research that aims to find phenomena, and the research design is descriptive design, which is research that aims to describe or visualize the phenomena that occur, whether natural or artificial, and the results of this research are considered more important for teachers to know Teaching methods with good vocabulary, including certainty, publication, abbreviation, review, settlement, and construction, which is called sculpting, until the learning process reaches the hand.